Vascular surgery within general surgery: an analysis of workload 1989-2005. - Ashraf, S; Bajwa, A; Magee, T; Galland, R (2007)
INTRODUCTION: There is considerable debate as to whether vascular surgery should be a subspecialty separate from general surgery. This study examines the changing relationship between general and vascular surgery in a district general surgical unit over 16 years. PATIENTS AND METHODS: A detailed survey of referrals, admissions and operations to one unit was carried out over 3 months in 2003. This was compared with similar surveys in 1989, 1990 and 1995. In addition a 3-month audit of operations performed was carried out in 2005 following a decision by the Primary Care Trust (PCT) to reduce varicose vein referrals. RESULTS: There was a significant increase in the number of varicose vein and arterial referrals 1989-2003 (P = 0.0001 and P < 0.0001, respectively). This was reflected in increased number of vascular admissions (P < 0.0001). In 1989, 14% of the arterial cases were admitted as emergencies. This figure rose to 52% in 2003 (P < 0.0001). There was a significant increase in the number of arterial operations performed between 1989 and 1995; however, from 1995 to 2003 this number fell P < 0.0001). The number of varicose vein procedures increased significantly 1989-2003 (P < 0.0001), with a significant fall after the PCT decision (P < 0.0001). However, the number of operations carried out in 2005 increased slightly with the proportion of general surgical cases, mostly hernia repairs and laparoscopic cholecystectomies, increasing. CONCLUSIONS: With increasing specialisation comes the risk that reduction in any aspect of a particular specialty may result in that unit becoming unsustainable. In vascular surgery this will inevitably lead to centralisation of services. In a large district general hospital having two general surgeons with a vascular interest, the general surgical component has maintained the workload of the unit following reduction in varicose vein referrals.